Learning in the Middle Years : More than a Transition - Groundwater-Smith, Susan ; Mitchell. Jane and Mockler, Nicole (South Melbourne Thomson Learning, 2007)
Takes up the varying perspectives of teachers, students and administrators and uses relevant Australian research to address challenges faced in teaching and learning in the middle years.
Include Reference and Index
Keywords: Learning, Psychology of -- Middle school education